A function is given below. Determine the average rate of change of the function

Algebra
Tutor: None Selected Time limit: 1 Day

g(x) = 


1
x
;    x = 1, x = a

g(x) = 

3
x + 6
;    x = 0, x = h

f(t) = 

3
t

;    t = at = a + h

Feb 16th, 2015

Please note that the rate r of change is:

1) function g(x) = 1/x

we have:

r = [g(1)-g(a)] / (a-1) = (1 - 1/a) / (1-a) = -1


2) function g(x) = 3/(x+6)

r = [g(h) -g(0)]  / (h-0) = [3/(h+6) - 3/6] / h = -1/(2*(h+6))


3) function f(t) = 3/t

r = [f(a+h)-f(a)]/(a+h-a) = [ 3/(a+h)- 3/a] / h=

r = -3/(a*(a+h))


Feb 16th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Feb 16th, 2015
...
Feb 16th, 2015
May 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer